Exposure and influence of TV programmes on Malay Community in Malaysia : testing selective exposure theory and third-person effect theory - Ismail, Rizalawati; Wok, Saodah; Azman, Zakirah (2012)

(untitled)
This study generally applies the selective exposure theory (Klapper, 1960) and third-person effect theory (Davison, 1983) to test the extent of TV viewing habits and TV influence on the Malay community with special emphasis on reality TV show. The objectives of the study are to identify Malay community exposure and preference of TV programmes, to gauge perceived TV influence on the Malay community, and to test the applicability of selective exposure theory and the third-person effect theory. This study employs a quantitative research design, using survey method, with questionnaire as the research instrument used for data collection. Pilot study has been conducted to pre-test the research instrument. The study is using cluster and stratified random sample, in which the stratified groups are based on state, gender, and age. The data were collected in March 2012. Data were analyzed using SPSS WIN 16 for descriptive statistics and inferential statistics to answer the objectives of the study and to test its hypotheses. The findings are expected to show TV viewing habits of the Malay community, their preferences to selected TV programmes, and the extent of watching reality TV shows. For general TV programmes, movies and comedy shows are the most preferred TV programmes, while sports and advertisements are the two least preferred TV programmes by the Malay community. Surprisingly, reality shows are not the most preferred TV programmes. Nevertheless, it is not the least preferred. Survivor, Master Chef, and Akademi Fantasia are the three most preferred reality TV shows, while Vokal Bukan Sekedar Rupa is the least preferred. In addition, the third- person effect can be proved by this study as the findings show that there is likelihood to perceive that TV programmes have an influence on others, specifically the Malay community, but not on themselves and their families.